Pengaruh Model Pembelajaran Peer Teaching Terhadap Peningkatan Aspek Afektif Mahasiswa Pada Mata Kuliah Akuntansi Keuangan Program Studi Perbankan Syariah Universitas Muhammadiyah Sumatera Utara - Isra Hayati; Dian Novianti Sitompul (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2017)
The purpose of this research is (1) to know the influence of peer teaching learning model to improve affective aspect of students in Financial Accounting course of Islamic Banking Study Program of Muhammadiyah University of North Sumatera (2) to know how big influence of peer teaching model to increasing affective aspect of student at Financial Accounting courses of Islamic Banking Studies University of Muhammadiyah Sumatera Utara. The method used in this research is quasi experiment with control group research pretest posttest design. After hypothesis testing by using Paired Sample T-Test technique, the significance (2-tailed) count is 0,001 at significance level <0,05 Thus H1 is accepted and H0 is rejected because of significance <0,05. So it can be concluded that there is influence of learning model of peer teaching on improving affective aspects of students in the subject of Financial Accounting courses of Islamic Banking University of Muhammadiyah North Sumatra. To see the improvement of the cognitive aspects achieved by the students used normalized N-Gain data. Improvement of student cognitive aspect that can be revealed, that is: mean of N-Gain score of affective aspect of student in experimental class 0,6593 whereas mean of N-Gain affective aspect of student in control class 0,4096. Improved affective aspects of students in the experimental and control classes belong to the moderate category.